Description of secondary effects in users of the etonogestrel implant in Honduras from March 2017 to May 2018 - José, Sophie (2020)
Introduction: The etonogestrel contraceptive implant is a modern method, which offers users contraceptive efficacy of up to 99% in a period of 3 years; it is safe comfortable and accessible. As all drugs have secondary effects, they are described as follows: amenorrhea, dysfunctional uterine bleeding, acne, nausea, and headache.Objective: To determine which are the most frequent secondary effects in users of the etonogestrel subdermal implant, in Tegucigalpa Honduras, from March 2017 to May 2018. Material and method: Descriptive, cross-sectional study of implant users in a polyclinic in Tegucigalpa, Honduras. The sample included women of childbearing age who voluntarily applied for the contraceptive implant to use it for the first time; the inclusion criteria were: use of the etonogestrel implant as a contraceptive method.Results: A total 115 women who met inclusion criteria were included. The most frequent secondary effect was amenorrhea, reported by 78 (68%), followed by headache 29 (25%), dysfunctional uterine bleeding 28 (24%), had other secondary effects such as weight gain, mastalgia, acne, nausea and others. Despite the secondary effects, 99 (86%) of women continue to use the implant and 109 (95%) of them would recommend it to other women for use as a contraceptive method.Conclusion: The most frequent secondary effect in users of the etonogestrel implant is amenorrhea, followed by headache and dysfunctional uterine bleeding.